PSYCHOLOGICAL CHARACTERISTICS OF EMPLOYEES OF THE MINISTRY OF INTERNAL AFFAIRS OF UKRAINE (MIA) - Chuhraeva, Anna (PSYCHOLOGICAL JOURNAL, 2019)
At the present stage of development of Ukraine, there is an increase in crime because of various reasons, including army hostilities in the east of the country. That is why the examined problem becomes really important. The issues of psychological support for police officers were studied by many scientists, but the integral concept of this problem has not been developed yet. We examined the 35-year old employees the Ministry of Internal Affairs with the help of the set of standardized psychological diagnostic techniques: Cattell’s Sixteen Personality Factor Questionnaire, Career Anchors Questionnaire, Rokeach Value Survey, Social intelligence of O.Sullivan, M.Guilford. It allowed us to assess the information value and prognostic validity of the proposed tests for the examined employees. According to the empirical study results, four groups of psychological characteristics for the employees of the Ministry of Internal Affairs can be distinguished: - employees’ professional-psychological orientation and sensitivity (desires, interests and the ability to understand psychological aspects of situations and people, ability to handle with them); - employees’ readiness to notice psychological aspects of effective professional actions and tactics, which manifests itself in understanding of the psychological conditions for effective professional work and the ability to create such conditions; in skilful use of psychological means (verbal and non-verbal) at professional work; in skilful use of the whole complex of psychological techniques, providing a high efficiency of operative-official task solution; - developed professional observation skills and memory (including the ability to apply psychologically sound techniques and rules for effective observation, developed professional attentiveness, trained sensory organs and perception, trained fast, complete and accurate memorization, good memorising and correct reproduction of significant information); - formed psychological stability (expressed in employees’ ability to act calmly and confidently in psychologically complex, emotionally tense, dangerous and highly responsible situations at operative-official task solution).